Organization structure and tribological study of hydrogel prepared by Uv light molding and casting molding methods for bionic articular cartilage - Yan, Chengqi; Chen, Junyue; Jia, Zhuying; Li, Zhanjun (Materials research express, 2023)
Hydrogels have similar structural and functional properties to natural articular cartilage, so they have been widely used in the research of biomimetic articular cartilage. In this research, polyvinyl alcohol (PVA) and betaine monomer were used as raw materials to prepare hydrogel on polyetheretherketone (PEEK) surface by Uv light molding and casting molding respectively. The results showed that two methods were used to prepare hydrogel film on PEEK surface successfully. The diameter of the internal hole of the hydrogel prepared by Uv light molding was larger than that prepared by casting molding. Compared with the hydrogels prepared by Uv light molding, the hydrogels prepared by casting molding have a lower friction coefficient because of their high load-carrying capacity. Different preparation methods seriously affect the formation of hydrogel structure. This study provides an important reference value for the preparation of high performance hydrogels.